"I don't know how musically creative they should be at that age": A qualitative study of parents' and teachers' beliefs about young children's creative and musical capacities. (September 2022) - MacGlone, Una; Wilson, Graeme; MacDonald, Raymond
There has been a recent expansion of school curricula and extra-curricular activities emphasizing musical creativity and collaboration. Parents have a crucial role in providing children with access to such experiences; their views on music and the nature of creativity influence the types of musical engagement their children will access. Teachers also have an important role, yet can have difficulties when supporting children in open-ended tasks. A qualitative study investigated parents' and teachers' constructions of creativity and music. Interviews were held with 11 parents and 4 teachers of preschool children who took part in improvisation workshops. Data were analyzed with thematic analysis, resulting in identification of three themes. Creativity and musicality were described as fundamental to children's "human nature" but positioned as a non-fundamental part of their own adult identities. "Values" explored conceptualizations of creativity through artistic products; musicality was appreciated demonstration of technical skill. "Frames for engaging" identified adults engaging with their children in creative tasks mainly through child-led narratives; in contrast, parents took on the role of "teacher" in musical tasks. Understanding these influential views offers insight into the types of activities and guidance offered to pre-schoolers and how they can be built on to foster children's musical creativity.